P64 Screening for hepatitis B prior to commencing rituximab – have we learnt from the past?. (19th June 2022) - Choon, Xin Yi; Turley, Rebecca; Hill, Stuart; Jumah, Wasan; Kooner, Paul; Kirby, Meera
Abstract : Introduction: Rituximab is associated with reactivation of the hepatitis B virus (HBV), as per the Medicines and Healthcare Products Regulatory Agency (MHRA) alert in December 2013, with documented cases of fulminant hepatitis, liver failure, and death. As such, screening for HBV is recommended prior to commencing Rituximab, and patients with positive serology for HBV should be referred to hepatology services. We set out to review compliance to the MHRA recommendations in a large district hospital. Method: All patients who received 1 or more doses of Rituximab between 1st April 2013 to 31 st March 2018 were included. Data were collected retrospectively from patient electronic databases, and included viral serology, liver function tests, and referral to hepatology services. Results: A total of 847 patients received Rituximab within our 5-year data collection period. The majority of prescriptions were from rheumatology (n= 286, 33.77%) and oncology (n= 546, 62.46%) departments. Of the 18 patients with positive serology (surface antigen and/or core antibody), 10 (55.56%) were tested after receiving the 1 st dose of Rituximab. 11 (61.11%) were referred for a hepatology review. We focused our efforts on the subgroup with an incomplete serological status but had received 1 or more Rituximab doses since January 2020. 38 patients met this criterion. The parent specialties were contacted directly and advised on urgent serological testing. Targeted training sessions have also been delivered to prescribers and pharmacists within the key specialties. Conclusions: Our data highlighted that rates of HBV screening prior to initiating immunosuppression with Rituximab were low. A higher proportion of patients were screened for active hepatitis B infection but not prior exposure, suggesting a partial understanding of HBV serology and the lifetime risk of reactivation. Our review also identified patients with absent or partial screens who continue to be at risk of HBV reactivation, such that retrospective testing could be performed urgently. Ongoing education of clinicians and implementation of national guidelines on a Trust level are both key to increasing HBV screening rates.